In vivo imaging of tau deposition in Alzheimer’s disease using both [18F]-THK5317 and [18F]-S16: A pilot human study - Fu, Liping; Zhang, Jinming; Zhou, Kaixiang; Zhang, Xiaojun; Xie, Hengge; Zhu, Mingwei; Cui, Mengchao; Wang, Ruimin (Frontiers in Aging Neuroscience, 2022)
Objective: To evaluate the effectiveness of a new tracer (S)-1-(4-(6-(dimethylamino)quinoxalin-2-yl)phenoxy)-3-fluoropropan-2-ol ([18F]-S16), in distinguishing patients with AD from HCs. Methods: Paired [18F]-S16 and [18F]-THK5317 scans were acquired in five patients with AD, six HCs, one subject with a semantic variant of primary progressive aphasia (sv-PPA) and one subject with probable progressive supranuclear palsy (PSP). Dynamic PET scanning was performed over 90 min after injection of the tracers. Standardized uptake values (SUV) and cortical-to-cerebellum standardized uptake value ratios (SUVRs) were used for tau deposition semi-quantization. A voxel-based analysis was employed to assess the uptake difference between populations. Results: [18F]-S16 exhibited excellent blood-brain-barrier penetration. AD patients showed increased cortical [18F]-THK5317 and [18F]-S16 binding. Compared to HCs, AD patients showed significantly increased cortical [18F]-S16 uptake in the bilateral occipital cortex, posterior cingulated cortex/precuneus, and lateral frontal cortex. Notable [18F]-S16 uptake was observed in the basal ganglia and brainstem compared to the neocortex. A substantial [18F]-S16 signal was detected in the basal ganglia and midbrain in a patient with probable PSP and in the bilateral anterior temporal cortex in a sv-PPA patient. Conclusions: [18F]-S16 might be of help to detect tau protein in vivo.